Profiling of rectal cancers MRI in pathological complete remission states after neoadjuvant concurrent chemoradiation therapy. Issue 3 (March 2016) - Kim, H.; Kim, H.M.; Koom, W.S.; Kim, N.K.; Kim, M.-J.; Kim, H.; Hur, H.; Lim, J.S.
Abstract : Aim: To fully characterise the magnetic resonance imaging (MRI) traits of rectal cancers in a large sample of patients, each experiencing pathological complete remission (pCR) after neoadjuvant concurrent chemoradiation therapy (CCRT). Materials and methods: A total of 120 patients (77 male, 43 female; median age, 59.5 years; range, 32–81 years) with rectal cancers in CCRT-induced pCR states who underwent pre- and post-CCRT MRI and eventual surgery between July, 2005 and September, 2014 were retrospectively reviewed. In most ( n= 100), diffusion-weighted imaging was also performed. Tumour volume, tumour regression grade (TRG), T-stage, mesorectal fascia (MRF) status, and T2 signal intensity (T2-SI) were analysed. Paired t -test and McNemar's test were applied for statistical comparisons. Results: Tumour volume declined sharply after CCRT (pre-CCRT, 21.5±22.4cm 3 ; post-CCRT, 6.6±8.4cm 3 ; p< 0.001). TRG distribution was as follows: G1 (clinical CR), 3; G2, 38; G3, 78; G4, 1; and G5 (marked progression), 0. Downstaging of T-stage (34%, 16/47) and MRF status (19.7%, 13/66) did occur; but on post-CCRT MRI, 25.8% (31/120) remained at T3≥5  mm or T4 stage, and 44.2% (53/120) were MRF-positive. A majority (88.3%, 106/120) of patients displayed intermediate T2-SI prior to CCRT. Most converted to dark T2-SI after CCRT, with 12.5% (15/120) unchanged. On post-CCRT MRI, 11% (11/100) of patients showed diffusion restriction. Conclusion: MRI findings in CCRT-induced pCR-status rectal cancers were highly variable. Tumour volume and T2-SI mostly decreased; however, such lesions occasionally presented with unexpected atypical features, such as large residual volume and/or intermediate T2-SI. Highlights: MR findings of pCR-achieved rectal cancer after CCRT are highly variable. The residual lesion of pCR-achieved rectal cancer often maintains large volume. pCR lesions mostly show decreased T2 SI, but sometimes intermediate SI remain.